Implementing Soil Health Improvement Techniques in Regenerative Agriculture Using IoT-Enabled NPK Sensing for Precision Nutrient Management - Alabdeli Haider; Obaid Mohammed Kadhim; Kumar C. Vivek (SHS Web of Conferences)
The goal of regenerative agriculture is to restore the ecological balance and the health of the soil through sustainable farming practices. With the addition of advanced technologies, EC-5 Soil Moisture Sensor, LoRaWAN, Atlas Scientific NPK Sensor Kit, Unmanned Aerial Vehicles (UAV), and Normalized Difference Vegetation Index (NDVI), this approach can be improved greatly. Real-time soil moisture data is acquired by the EC-5 sensor, which helps in precise irrigation management working for soil structure and microbial health. Continuous and long-range communication technology comes with LoRaWAN technology for the remote monitoring of soil conditions in large parts of the agricultural area. The Atlas Scientific NPK Sensor Kit can be used to do accurate nutrient analysis, and as such, you get targeted and efficient nutrient application that results in increased soil fertility as well as lower environmental impact. In addition, aerial assessment of crop health and soil status as provided by UAVs with imaging sensors and NDVI data derived from such UAVs aid in making more informed decisions regarding soil and crop management. This paper describes how these technologies can be implemented and used in the context of regenerative agriculture, viz., the roles they play, the functions they perform, and their importance in increasing the health of the soil. The paper introduces solutions to the problems of soil health and the principles of regenerative agriculture. Then, it moves on to detailing the incorporation of each technology, stressing its undeniable impact on soil moisture management, nutrient cycling, and the entire ecosystem's sustainability. The description is given of the experimental setup and methodology, and data collected and their results are analyzed. The paper ends by evaluating what effect these technologies have on soil health and recommendations for continuing research work and applications in regenerative agriculture. The findings emphasize the possibility of the joint application of modern technology with regenerative practices to restore great lengths of time, increase biodiversity, and increase sustainable agricultural productivity. A 12%, 15%), and 10% improvement in soil moisture retention, a 15% increase in soil organic carbon, and a 10% reduction in nutrient runoff were observed in the results. Furthermore, crop yields increased by 8%, and soil respiration rates were elevated by 5 mg CCk/kg soil/day, indicating the aptitude of the developed technologies in improving soil health and productivity.